Transient neonatal diabetes mellitus caused by a gene mutation - Jung Hyun Kong; June Bum Kim (Korean Pediatric Society, 2011)
Transient neonatal diabetes mellitus (TNDM) is a rare form of diabetes mellitus that presents within the first 6 months of life with remission in infancy or early childhood. TNDM is mainly caused by anomalies in the imprinted region on chromosome 6q24; however, recently, mutations in the ABCC8 gene, which encodes sulfonylurea receptor 1 (SUR1), have also been implicated in TNDM. Herein, we present the case of a male child with TNDM whose mutational analysis revealed a heterozygous c.3547C>T substitution in the ABCC8 gene, leading to an Arg1183Trp mutation in the SUR1 protein. The parents were clinically unaffected and did not show a mutation in the ABCC8 gene. This is the first case of a de novo ABCC8 gene mutation in a Korean patient with TNDM. The patient was initially treated with insulin and successfully switched to sulfonylurea therapy at 14 months of age. Remission of diabetes had occurred at the age of 16 months. Currently, the patient is 21 months old and is euglycemic without any insulin or oral hypoglycemic agents. His growth and physical development are normal, and there are no delays in achieving neurological and developmental milestones.